Transaxillary transcutaneous aortic valve implantation (TAVI)—our first case reports - Glavnik Poznič Nina; Balevski Igor; Robič Boris; Fluher Jure; Kučič, Jože; Kanič, Vojko (Acta Medico-Biotechnica, 2023)
In the past decade, the incidence of severe aortic stenosis has been high because of population aging. Guidelines have recommended transfemoral transcutaneous aortic valve implantation (TAVI) for a wider patient population, because of technical improvements and increased experience among physicians. Peripheral artery disease often accompanies aortic stenosis and is an important contraindication for transfemoral TAVI. Currently, new access sites for TAVI are used in cases with high surgical risk. We performed the first two axillary TAVI procedures at our institution. The two patients are described in this case report.